genotoxicity produced in the epithelial cells of the oral cavity and Comet assay in urinary tract of workers in aluminum factories - Sarab Dalaf Khalaf; Wajdi Sabeeh Sadeq (Tikrit Journal of Pure Science)
Whilst being environmentally abundant, aluminum is not essential for life. On the contrary, aluminum is a widely recognized neurotoxin that inhibits more than 200 biologically important functions and causes various adverse effects in plants, animals, and humans. The acute toxicity of aluminum is low. No acute effects due to dietary exposure to aluminum have been observed in the general population. A compendium is provided of aluminum compounds used in industrial settings, and as pharmaceuticals, food additives, cosmetics and as other household products. In our current study, the genotoxicity of aluminum was evaluated in epithelial cells by Micronucleus assay in buccal cells and Comet assay in urinary tract cells, 50 samples were taken from the workers in the aluminum factory and 50 samples as control. The results showed significant increased in the average of the affected cells (8.86 ± 1.36) and the average total cell total (51.66 ± 18.19)  in urinary tract while the average of damage cells (72.02 ± 8.99) and It is noted that the mean micronuclei (1.61±29.80) and the average abnormality in all cells (3.06 ±92.54) while the Mni(51.28 ±10.61). These results suggest that the estimation of cellular genetic damage in epithelial cells by Micronucleus assay and Comet assay estimation is important to know the toxic effects of aluminum.